Normative Analysis of Incest Sanctions in Mandailing Customary Law from an Islamic Criminal Law Perspective - Fadilah, Nurul; Sukiati, Sukiati (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
Incestor incestuous sexual relations are acts that are prohibited by law, including customary law and Islamic law. The prohibition of incest in the legal context is categorized as a crime that damages the basic social order of society. This study aims to explore how sanctions are applied to incest perpetrators in the context of Mandailing customary law and Islamic criminal law. This research adopts a qualitative approach in its research methodology. Data was collected using interview techniques extracted from sources in the field. This study concludes that the legal sanction for perpetrators of incest according to Mandailing customary law is by expelling the perpetrator of the crime of incest from his village. According to Islamic criminal law, the sanction imposed on married perpetrators of incest crimes is the death penalty, and unmarried perpetrators are punished by flogging and exile. Compared to Islamic law, the sanctions for implementing customary law in Mandailing can be considered lighter. It is hoped that this study will provide an overview of the variations in decision-making regarding the crime of incest under different laws. This study is also expected to contribute to the development of legal discourse in society, especially customary law on the one hand and Islamic legal perspectives on the other.